Foot and Leg Muscle Weakness in People With Midfoot Osteoarthritis. Issue 6 (3rd June 2021) - Arnold, John B.; Halstead, Jill; Grainger, Andrew J.; Keenan, Anne‐Maree; Hill, Catherine L.; Redmond, Anthony C.
Abstract : Objective: To compare foot and leg muscle strength in people with symptomatic midfoot osteoarthritis (OA) with asymptomatic controls, and to determine the association between muscle strength, foot pain, and disability. Methods: Participants with symptomatic midfoot OA and asymptomatic controls were recruited for this cross‐sectional study from general practices and community health clinics. The maximum isometric muscle strength of the ankle plantarflexors, dorsiflexors, invertors and evertors, and the hallux and lesser toe plantarflexors was measured using hand‐held dynamometry. Self‐reported foot pain and foot‐related disability were assessed with the Manchester Foot Pain and Disability Index. Differences in muscle strength were compared between groups. Multivariable regression was used to determine the association between muscle strength, foot pain, and disability after adjusting for covariates. Results: People with midfoot OA (n = 52) exhibited strength deficits in all muscle groups, ranging from 19% (dorsiflexors) to 30% (invertors) relative to the control group (n = 36), with effect sizes of 0.6–1.1 ( P < 0.001). In those with midfoot OA, ankle invertor muscle strength was negatively and independently associated with foot pain (β = –0.026 [95% confidence interval (95% CI) –0.051, –0.001]; P = 0.045). Invertor muscle strength was negatively associated with foot‐related disability, although not after adjustment for depressive symptoms (β = –0.023 [95% CI –0.063, 0.017]; P = 0.250). Conclusion: People with symptomatic midfoot OA demonstrate weakness in the foot and leg muscles compared to asymptomatic controls. Preliminary indications from this study suggest that strengthening of the foot and leg muscles may offer potential to reduce pain and improve function in people with midfoot OA.